Penerapan Metode Tutor Sebaya (peer tutor) untuk Meningkatkan Hasil Belajar Siswa pada Materi Komposisi Fungsi - Kamilah, Fiisyatil; Hidayah, Shofia; Istriningsih (Papanda, 2025)
This study is a Classroom Action Research that applies the Peer Tutor method to improve students’ mathematics learning outcomes on the topic of function composition. The Peer Tutor method is a learning approach that involves higher-achieving students assisting their classmates in understanding the material and completing learning tasks. The problem addressed in this research is the low learning outcomes and lack of student engagement. The study was conducted in two cycles, and each cycle consisted of four stages: planning, implementation, observation, and reflection. The subjects of this research were 24 students of class XI D. The data were analyzed using comparative quantitative descriptive analysis. In the pre-cycle stage, students’ average score was 59.13 with a mastery learning percentage of 37.5%. After implementing the Peer Tutor method in Cycle I, the average score increased to 76.45 with a mastery percentage of 62.5%. In Cycle II, the average score reached 86.67 with 100% mastery learning. The results indicate that the application of the Peer Tutor method can improve students’ learning outcomes and engagement in mathematics, particularly in the topic of function composition.